INPUT-OUTPUT ANALYSIS OF SUGARCANE PLANTATION IN INDONESIA - , FATKHIYAH ROHMAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of study are: (1) to understand the value of domestic transaction of sugarcane upstream and downstream industry on Indonesian economy, (2) to measure the backward and forward linkage of sugarcane plantation on Indonesian economy, (3) to estimate the multiplier effects on output, income, employment and gross added value of sugarcane plantation. Input-Output analysis is used to analyse domestic transactions based on producer price of Input- Output data that is 66 sectors classified, published by Central Statistic Agency. The study show that five biggest value of domestic transaction by sugarcane plantation upstream industry are fertilizers and pesticides, building, financial institutions, trade and land transport, while the downstream industry are sugar industry, livestock, restaurants and hotels, beverages industry and other food industry. Backward and forward linkage of sugarcane plantation is over the average of all agriculture sectors. Dispersion coefficient of sugarcane plantation under the average of all agriculture sectors while dispersion sensitivity is over the average of agriculture sectors. Output multiplier and income multiplier of sugarcane plantation is over the average of all agriculture sectors while gross added value and employment is under the average of all agriculture sectors on Indonesian economy. Gross added value and the absorption of employemnt have to be increased.